Long-term sewage sludge application in a tropical Oxisol: Effects on acidity and availability of micronutrientes - Mariângela B. Freiberger; Gustavo Castoldi; Silvia Capuani; Diego O. Ribeiro; Fabiano G. Silva; Leonardo T. Büll (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the effects of acidity and availability of micronutrients on a sandy clay loam Oxisol grown with soybeans (summer) and black oat (autumn/winter), after long-term applications of biodigested sewage sludge (BS) and centrifuged sewage sludge (CS). The experiment was conducted in Botucatu, SP, Brazil, from 2002 to 2014, using a randomized block design, in 2×4 factorial scheme, with four repetitions. Treatments corresponded to six biennial applications of BS and CS at four doses: 0, 2, 4 and 8 Mg ha-1 (dry basis). Soil samples up to 0.60 m depth were taken after twelve years, and pH, potential acidity, exchangeable acidity and micronutrient contents were evaluated. The CS applications of 4 and 8 Mg ha-1 led to pH values within the recommended range up to depths of 0.10 and 0.20 m, respectively, whereas BS applications did not result in adequate pH values in any layer. The increased soil pH caused by CS applications resulted in a proportional reduction in soil potential acidity, whereas BS applications resulted in high value of potential acidity (70 mmolc dm-3) in all layers. The CS applications resulted in low Al3+ concentrations up to 0.20 m depth, whereas BS applications led to high Al3+ concentrations from the 0.05-0.10 m layer. The successive applications of both sludges resulted in Cu2+, Fe2+, Mn2+ and Zn2+ concentrations that exceeded the maximum values allowed in all soil layers. Low boron concentrations were found in the soil, and pH was the determinant factor for it.